Aceh pungo - Al Mubarak, Taufik, 1981- (Banda Aceh, Aceh, Indonesia : Bandar Publishing, 2009)
Contemporary issues of social change in Aceh; collected articles.
Keywords: Nanggroe Aceh Darussalam (Indonesia) -- Social conditions; Nanggroe Aceh Darussalam (Indonesia) -- Politics and government